The Retreatism Process of Hikikomori People on the Example of 24 Japanese Hikikomori Clients - Karolina Aleksandra Kalita (Seminare, 2019)
In this publication I present a fragment of the results of my doctoral thesis, in which assuming in the sociological perspective that I am dealing with an example or a form of one of five types of adaptation to the situation of anomie named by the American sociologist Robert K. Merton: “retreatism’’, on the example of 24 Japanese Hikikomori clients, described a problem being at the center of my scientific interests - the Shakaiteki Hikikomori (Eng. Social Withdrawal) in Japan (i.a. the profile of Hikikomori person, the retreatism process of Hikikomori people, the socio-cultural factors favoring the retreatism option in the form of Hikikomori etc.) More specifically, in this publication I present the retreatism process of Hikikomori people.